1982
DOI: 10.1055/s-2007-971450
|View full text |Cite
|
Sign up to set email alerts
|

Oléo-Résine d'Aucoumea klaineana

Abstract: From oleoresin of Aucoumea klaineana Pierre, five triterpenes are isolated; one pentacyclic triterpene: alpha-amyrin and four tetracyclic triterpenes: masticadienediol which seems to be new in this family, 3alpha-hydroxytirucalla-8,24-dien-21-oic acid, 3 alpha-hydroxytirucalla-7,24-dien-21-oic acid which have been already isolated in some Burseraceae and 3-oxotirucalla-7,24-dien-21-oic acid which seems to be a new triterpene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 4 publications
(4 reference statements)
0
10
0
2
Order By: Relevance
“…H] + ), accounting for 8 degrees of unsaturation. Accordingly, compound 2 was established as 3-oxotirucalla-7,24-dien-21-oic acid, a tirucallane triterpene first isolated from oleoresin of Aucoumea klaineana (Tessier et al, 1982) and later identified in Xanthoceras sorbifolia (Ma et al, 2000), Rhus javainica L. (Lee et al, 2005), Pancovia pedicellaris (Soh et al, 2009), and Feroniella lucida (Sriyatep et al, 2014), which displays inhibitory activity against HIV-1 protease (Ma et al, 2000;Nimmanpipug et al, 2009) and cytotoxicity (Lee et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H] + ), accounting for 8 degrees of unsaturation. Accordingly, compound 2 was established as 3-oxotirucalla-7,24-dien-21-oic acid, a tirucallane triterpene first isolated from oleoresin of Aucoumea klaineana (Tessier et al, 1982) and later identified in Xanthoceras sorbifolia (Ma et al, 2000), Rhus javainica L. (Lee et al, 2005), Pancovia pedicellaris (Soh et al, 2009), and Feroniella lucida (Sriyatep et al, 2014), which displays inhibitory activity against HIV-1 protease (Ma et al, 2000;Nimmanpipug et al, 2009) and cytotoxicity (Lee et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of 13 C-NMR data of 2 with 3 -hydroxytirucalla-7,24-dien-21-oic acid ( -elemolic acid) (3) (Guang-Yi et al, 1988;Tessier et al, 1982;Cotterrell et al, 1970) showed good agreement except for a keto group at C-3 ( C 217.1) in 2, instead of a secondary alcohol group ( C 74.2) in 3. These observations suggest that 2 differed from 3 only in oxidation of the 3 -hydroxyl function to the corresponding 3-oxo.…”
Section: Resultsmentioning
confidence: 99%
“…3) were initially isolated from Manila elemi and are not systematically present in elemi resin (Cotterell et al . 1970; Tessier et al . 1982; Guang‐Yi et al .…”
Section: Resultsmentioning
confidence: 99%
“…Similar tirucallane compounds have previously been isolated from elemi resin (Arigoni et al, 1995;Coterrell et al, 1970;Argay et al, 1997), which is produced by a Burseraceae tree from the Philippine Islands. It has also been reported as a constituent of the oleoresin of Aucoumea klaideana, a large tree from equatorial Africa (Tessier et al, 1982;Guang-Yi et al, 1989). New tirucallane triterpenes have recently been reported as constituents of the bark of Dysoxylum macranthum, a Meliaceae tree from New Caledonia (Mohamad et al, 1999).…”
Section: Commentmentioning
confidence: 93%